La parentalité sacrificielle Sens de la pratique d'abandon volontaire d'enfants en Haïti - Billy, Raynold (Psychologies et Société, 2023)
This book analyses the motivations and experiences of Haitian parents who have given up a child for international adoption. The parents' accounts describe the decision to abandon as a rescue project rather than a refusal or denial of parenthood.